Representing Cyberbullying Perpetrators in Indonesian Digital Media: A Critical Discourse Analysis of the Jakarta Post - Erika Agustiana (Universitas Islam Negeri Palopo, 2026)
This study examines how cyberbullying perpetrators are portrayed in Indonesian digital media through a Critical Discourse Analysis (CDA) of